Social meanings and understandings in patient-nurse interaction in the community practice setting: a grounded theory study - Stoddart Kathleen M (BMC, 2012)
Abstract Background The patient-nurse relationship is a traditional concern of healthcare research. However, patient-nurse interaction is under examined from a social perspective. Current research focuses mostly on specific contexts of care delivery and experience related to medical condition or illness, or to nurses' speciality. Consequentially, this paper is about the social meanings and understandings at play within situated patient-nurse interaction in the community practice setting in a transforming healthcare service. Methods Grounded theory methodology was used and the research process was characterised by principles of theoretical sensitivity and constant comparative analysis. The field of study was four health centres in the community. The participants were patients and nurses representative of those attending or working in the health centres and meeting there by scheduled appointment. Data collection methods were observations, informal interviews and semi-structured interviews. Results Key properties of 'Being a good patient, being a good nurse', 'Institutional experiences' and 'Expectations about healthcare' were associated with the construction of a category entitled 'Experience'. Those key properties captured that in an evolving healthcare environment individuals continually re-constructed their reality of being a patient or nurse as they endeavoured to perform appropriately; articulation of past and present healthcare experiences was important in that process. Modus operandi in role as patient was influenced by past experiences in healthcare and by those in non-healthcare institutions in terms of engagement and involvement (or not) in interaction. Patients' expectations about interaction in healthcare included some uncertainly as they strived to make sense of the changing roles and expertise of nurses and, differentiating between the roles and expertise of nurses and doctors. Conclusions The importance of social meanings and understandings in patient-nurse interaction is not fully apparent to nurses, but important in the patient experience. Seeking understanding from a social perspective makes a contribution to enhancing knowledge about patient-nurse interaction with subsequent impact on practice, in particular the development of the patient-nurse relationship. The implications are that the meanings and understandings patients and nurses generate from experiences beyond and within their situated interaction are pivotal to the development of their relationship in the transforming community healthcare environment.